(untitled) (Journal of Information Technologies in Education (ITE), 2010)
In article basic aspects introduction integrated environment verification knowledge students from microeconomic are expounded. It is considered structure of Decision Environmental with the built-in program modules (mathematical and graphical editors) for the decision of typical assignments from microeconomics during the current and final control of students’ knowledges of different forms of teaching.